Internet Facilities Utilisation and Undergraduate Students’ Academic Performance of Federal Colleges of Education in North Central Nigeria - Ramson, Emmanuel Nannim; Katkukah, Danjuma Gokum; Ajayi, Daniel Oluwafeyikemi (NIU Journal of Humanities, 2018)
The study was an assessment of undergraduate students’ utilization of internet facilities for academic purpose in the Federal Colleges of Education in North central Nigeria. In achieving the goals of the study, four research questions and two hypotheses were raised. The study employed the cross-section survey research design approach in which both descriptive statistics and the Pearson-chi-square statistical tools were used in analyzing the research questions and hypotheses raised. The study also used the questionnaire for internet users (QIU) as tool for data collection from the sample of NCE and B.Ed undergraduate students of F.C.E. in North central Nigeria to which the stratified random sampling technique was employed in selection of respondents. Results of data analysis from the study shows that there is a significant difference in the internet literacy/exposure level; amount of time spent on the internet for academic purpose; and extent of utilization of internet facilities for academic purpose among the NCE and B.Ed undergraduate students of the Federal Colleges s of Education in North central Nigeria.